Coaching and training transfer: A phenomenological inquiry into combined training-coaching programmes - Linda Spencer (International Journal of Evidence Based Coaching and Mentoring, 2011)
Businesses often turn to coaching to combat under-performance in training transfer, i.e. the translation of learning from training into improved performance in the workplace. This article reports on a phenomenological study of the experiences of seven professional external coaches working on combined training-coaching leadership development or management skills programmes. The findings suggest that coaching supports training transfer, but not necessarily in the ways that established transfer models predict. Synergistic effects emerged from combining training and coaching. The coach’s interpretation of their role had a significant influence on transfer effects. The study serves to inform coaches’ practice and contribute to more effective programme design.